2002
DOI: 10.1074/jbc.m106974200
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker Channels Produce an Instantaneous Current

Abstract: Spontaneous rhythmic activity in mammalian heart and brain depends on pacemaker currents (I h ), which are produced by hyperpolarization-activated cyclic nucleotide-gated (HCN) channels. Here, we report that the mouse HCN2 pacemaker channel isoform also produced a large instantaneous current (I inst(HCN2) ) in addition to the well characterized, slowly activating I h . I inst(HCN2) was specific to expression of HCN2 on the plasma membrane and its amplitude was correlated with that of I h . The two currents had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 43 publications
13
114
1
Order By: Relevance
“…Accili and his colleagues have suggested that the expression of HCN2 channels is associated with the expression of an "instantaneous current" that is voltage insensitive over the tested voltage range and the magnitude of which is directly proportional to the amount of heterologously expressed HCN protein and that increased on coexpression with the regulatory subunit minK-related peptide 1 (Macri and Accili 2004;Proenza et al 2002). These authors concluded that HCN channels mediate a voltage-insensitive, instantaneous current through leaky channels.…”
Section: Assessment Of Three Methods For Isolating I Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Accili and his colleagues have suggested that the expression of HCN2 channels is associated with the expression of an "instantaneous current" that is voltage insensitive over the tested voltage range and the magnitude of which is directly proportional to the amount of heterologously expressed HCN protein and that increased on coexpression with the regulatory subunit minK-related peptide 1 (Macri and Accili 2004;Proenza et al 2002). These authors concluded that HCN channels mediate a voltage-insensitive, instantaneous current through leaky channels.…”
Section: Assessment Of Three Methods For Isolating I Hmentioning
confidence: 99%
“…It has recently been demonstrated that in an expression system, the expression of g h is associated with a voltageinsensitive conductance, an instantaneous current (Macri and Accili 2004;Proenza et al 2002). If the expression of a voltage-sensitive g h is associated with a voltage-insensitive conductance in T and D stellate cells, then the magnitude of the voltage-insensitive, ZD7288-sensitive conductance would be expected to be related to the voltage-sensitive conductance.…”
Section: Voltage-insensitive Zd7288-sensitive Conductancementioning
confidence: 99%
“…9). This is not altogether surprising when one considers that HCN2 channels are partially open at this potential (Chen et al, 2001a) and may generate a voltage-independent current (Proenza et al, 2002;Macri and Accili, 2004;Proenza and Yellen, 2006). Another possible explanation for this effect is poor dendritic voltage control when recording from the soma, which could result from the nonisopotentiality of RTN neurons (Destexhe et al, 1996).…”
Section: Hcn2 Channels and Glur4-containing Ampa Receptors Are Presenmentioning
confidence: 98%
“…3A). The difference in sensitivities has been attributed to at least two open states for HCN2 channels, one a "leaky" open state permeable to Cs + and the other a "normal" hyperpolarization-activated state sensitive to Cs + (Proenza et al 2002).…”
Section: Figmentioning
confidence: 99%